Reconstructing State Economic Loss Calculation in Corporate Corruption Adjudication - Anastasia Rentama Sijabat (Transpublika Publisher, 2026)
Indonesian anti-corruption adjudication continues to grapple with inconsistent quantification of state financial loss in corporate corruption cases. This study examined two recent cassation rulings of the Indonesian Supreme Court involving the palm oil industry and analyzed them against two 2026 rulings of the Constitutional Court that reaffirmed the exclusive declaring authority of the Supreme Audit Agency and entrenched the actual loss principle. Using a normative juridical design, the analysis combined statute, case, and conceptual approaches, complemented by comparative insights from the French Sapin II framework and the Spanish recovery model. The evidence indicated a methodological disorientation, namely that the same court relied on a proceeds-oriented calculus in one ruling and a loss-oriented calculus in another, even though the underlying fact patterns were materially comparable. This oscillation has eroded legal certainty and weakened the deterrent function of corporate criminal liability. To address this and to harmonize practice with the new constitutional jurisprudence, the discussion proposed an Integrated Economic and Ecological Audit Standard, configured as a three-layer architecture in which the Supreme Audit Agency declares, supporting institutions supply technical valuations, and the trial court independently validates. Five components, comprising unlawful gain, direct fiscal loss, ecological recovery cost, downstream economic loss, and social cost, are reframed as quantifiable financial figures within the broader umbrella of state economic loss. The findings suggested that consistent adoption of this architecture could systematize judicial reasoning, improve recovery rates, and tighten corporate accountability, offering practitioners and lawmakers a coherent doctrinal template.